MAKING OF CHEMICAL LITERACY ORIENTED CHEMPOINTS LEARNING MEDIA ON ACID-BASE MATERIAL - Desi Latipah Fauziah; Imelda Helsy; Cucu Zenab Subarkah (Gunung Djati Conference Series, 2021)
This research aimed to produce chempoints learning media oriented to chemical literacy on acid-base material and to determine the validation of the game’s effectiveness as a media for learning chemistry on acid-base material. Chempoints is an educational game adapted from a scrabble game with modifying the appearance and rules of the game by linking the material studied. Making media with Design Based Research included the stages of analysis, design and development. Product validation assessments were obtained from chemist and multimedia experts validators. The data collection technique used a questionnaire with a Likert scale. The data analysis technique used descriptive statistical analysis. The results showed that for all items and aspects measured, the validity assessment of chemical literacy oriented chempoints learning media on acid-base material obtained valid and good criteria with an average value of rcount of 0.86. Based on the results of the study, it can be concluded that the chempoints learning media oriented to chemical literacy is suitable for use in learning chemistry on the acid-base material.